Jazz funeral: a Skip Langdon novel - Smith, Julie (Fawcett Columbine, 1993)
Smack in the middle of the summer, Skip finds herself investigating the stabbling death of the universally beloved producer of the New Orleans Jazz and Heritage Festival. Then the victim's sixteen-year-old sister disappears, and Skip suspects that if the young woman isn't herself the murderer, she's in mortal danger from the person who is. And with her long-distance love, Steve Steinman, and her landlord, Jimmy Dee, to assist her, Skip trails an elusive killer through the delirium of a city caught up in the world's most famous music bash....
Keywords: Mysteries